2017
DOI: 10.5897/ajar2016.11654
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of a degraded ultisol with hardwood biochar: Effects on soil physico-chemical properties and yield of cucumber (Cucumis sativus L)

Abstract: A study was conducted in two consecutive cropping seasons to assess the effect of biochar on soil properties and yield of cucumber (Cucumis sativus L) in an intensive cucumber-maize rotation based system of Abakaliki, Southeastern Nigeria. Five rates of hardwood biochar (0, 2.5, 3.75, 5 and 6.25 t ha -1 ) were used for the study. The study was laid out as a randomized complete block design (RCBD) with five treatments and four replications. Data were collected from both soil and plant parameters. Soil samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…On the other hand, the shortest cucumber vine length was observed in plots treated with PKHB only (84.4 cm), followed by the control (103.4 cm). This study's findings are consistent with the report by Mbah et al (2017), who observed a significant increase in cucumber vine length when soils were treated with a 5 t/ha rate of hardwood biochar. However, there were some differences between the studies.…”
Section: Vine Lengthsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the shortest cucumber vine length was observed in plots treated with PKHB only (84.4 cm), followed by the control (103.4 cm). This study's findings are consistent with the report by Mbah et al (2017), who observed a significant increase in cucumber vine length when soils were treated with a 5 t/ha rate of hardwood biochar. However, there were some differences between the studies.…”
Section: Vine Lengthsupporting
confidence: 92%
“…The studies conducted by Mbah et al (2017) in Abakaliki, southeastern Nigeria, and Upadhyay and Neupane (2020) in Khumaltar, Nepal, support the results of this study. Their research reported a significant increase in cucumber leaves, lettuce, and potatoes when amended with biochar.…”
Section: Number Of Leavessupporting
confidence: 85%
“…The high soil pH in the amended plots is attributed to high Ca, Mg and K associated with the rice-mill waste whose effect on the soil can be likened to that of lime (Lickaz 2002). Mbah et al (2017) reported that soil pH increases following organic waste application.…”
Section: Soil Phmentioning
confidence: 99%
“…In many African countries, soil fertility levels have been declining since the past three to four decades (Stoorvogel and Smaling 1990a;Cobo et al 2010;Ukaegbu et al 2015;Mbah et al 2017;Nwite et al 2019), partly as a consequence of the high population pressure (Gebresamuel et al 2020;Okolo et al 2019) which makes farmers abandon the traditional practice of using fallow to restore soil fertility. Moreover, the intensity of farming on steep slopes has increased, especially in Ethiopia where areas exceeding 16% slope are being cultivated (Corbeels et al 2000;Amede et al 2001;Abegaz et al 2007;EIAR and TARI 2011).…”
Section: Introductionmentioning
confidence: 99%